Penyuluhan Tentang Status Gizi pada Remaja untuk Mencegah Stunting - Miftah Chairunnisa; Khairulisni Saniati; Silvia Finida Hannisa; Arum Seftiani Lestari; Asri Fitri Yati; Dian Ika Pratiwi (Institut Teknologi dan Bisnis Semarang, 2025)
Stunting is a target of the Sustainable Development Goals (SDGs) which aims at sustainable development number 2, namely eliminating hunger and all forms of malnutrition by 2030 and achieving food security. The activity was carried out at the Hisbah Al-Fatih Islamic Boarding School in Sintang Regency, West Kalimantan. The target of this community service activity was 39 female adolescents. This activity was carried out with a pretest and posttest. The material presented was the definition and characteristics of stunted children, the causes of stunting and how to prevent stunting. Based on the results of the measurement, it showed that adolescents understood after being given counseling activities.